The Influence of Electronic Word of Mouth (eWOM) on TikTok on Purchase Intention of Azarine Serum Beauty Products at Wahana Kosmetika Indonesia - Nabila Dafiya Azhar; Dorothy Rouly Haratua Pandjaitan; Mudji Rachmat Ramelan (Harmony Management: International Journal of Management Science and Business, 2025)
In the current digital era, consumer perceptions and decisions can be influenced by social media, one of which is TikTok, in the dissemination of information through Electronic Word of Mouth (eWOM) which can influence consumer behavior. This study aims to analyze eWOM on TikTok towards the purchase intention of Azarine serum products using the Information Adoption Model (IAM) approach. This model examines how information quality, information quantity, and information credibility affect the usefulness of information which then has an impact on information adoption and purchase intention. This study was conducted with a quantitative approach, where data was collected by distributing questionnaires to respondents who were TikTok users and had been exposed to Azarine serum content. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS software. The results showed that information quality did not have a positive and significant effect on the usefulness of information, while information quantity and information credibility had a positive and significant effect on the usefulness of information. Furthermore, the usefulness of information had a positive and significant effect on information adoption and information adoption had a positive and significant effect on purchase intention. These findings emphasize the importance of information characteristics in shaping consumer decisions and can be a reference for companies in designing more effective digital communication strategies on social media.